Characterization of gaseous pollutants and PM2.5 at fixed roadsides and along vehicle traveling routes in Bangkok Metropolitan Region - Oanh, N. T. Kim; Kongpran, J.; Hang, N. T.; Parkpian, P.; Hung, N. T. Q.; Lee, S. -B.; Bae, G. -N. (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Traffic is a major source of air pollution in urban areas of developing countries that leads to high exposure risk of urban dwellers. This study comparatively investigated levels of fine particles (PM2.5), SO2, NO2, and BTEX (benzene, toluene, ethylbenzene and xylenes) at fixed roadsides and on traveling routes in congested urban and less congested suburban areas of Bangkok in 2010. The roadside air quality monitoring was done at two opposite sites across the selected roads. The traffic counting was made simultaneously in these roads and hourly flows of 8 different vehicle types were determined. Roadside PM2.5 levels during dry season were high in both the city center and suburban area, significantly above the wet season, with 65-75% measurements exceeded 24 h Thailand ambient air quality standard of 50 mu g m(-3). Oppositely, roadside BTEX levels measured in the city center during wet season were higher than dry season and well above those in suburban area. Diurnal variations and the results of SPSS (Statistical Package for the Social Sciences) analysis showed associations between roadside pollutants levels and hourly traffic flows. The differences in pollution levels between 2 monitoring sites across a road were explained by road configurations and prevalent wind directions. On-route pollution levels were measured simultaneously both inside and outside selected vehicles (van, pickup), and on motorcycle. The on-route PM2.5 levels along the urban route were higher during the dry season than wet season. PM2.5 levels inside the vehicles were lower than outside whereas the opposite was observed for BTEX. BTEX were higher on more congested urban sub-routes with lower vehicle speeds. Higher pollution levels suggest a high risk of exposure. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: PARTICULATE AIR-POLLUTION; ORGANIC-COMPOUNDS; EMISSIONS